Trends in climatically driven extreme growth reductions of Picea abies and Pinus sylvestris in Central Europe. (17th October 2021) - Treml, Václav; Mašek, Jiří; Tumajer, Jan; Rydval, Miloš; Čada, Vojtěch; Ledvinka, Ondřej; Svoboda, Miroslav
Abstract: Extreme tree growth reductions represent events of abrupt forest productivity decline and carbon sequestration reduction. An increase in their magnitude can represent an early warning signal of impending tree mortality. Yet the long‐term trends in extreme growth reductions remain largely unknown. We analyzed the trends in the proportion of trees exhibiting extreme growth reductions in two Central‐European conifer species— Pinus sylvestris (PISY) and Picea abies (PCAB)—between 1901 and 2018. We used a novel approach for extreme growth reduction quantification by relating their size to their mean recurrence interval. Twenty‐eight sites throughout Czechia and Slovakia with 1120 ring width series representing high‐ and low‐elevation forests were inspected for extreme growth reductions with recurrence intervals of 15 and 50 years along with their link to climatic drivers. Our results show the greatest growth reductions at low‐elevation PCAB sites, indicating high vulnerability of PCAB to drought. The proportions of trees exhibiting extreme growth reductions increased over time at low‐elevation PCAB, decreased recently following an abrupt increase in the 1970–1980s at high‐elevation PCAB, and showed nonsignificant trends in high‐ and low‐elevation PISY. Climatic drivers of extreme growth reductions, however, shifted over time for all site categories as the proportion of low‐temperature‐induced extreme growth reductions declined since the 1990s, whereas events caused by drought consistently increased in frequency during the same period. We observed higher growth volatility at the lower range of distribution compared with the upper range margin of PISY and PCAB. This will undoubtedly considerably impact tree growth and vitality as temperatures and incidence of drought in Central Europe are expected to further increase with ongoing climate change. Abstract : Low‐elevation P. abies exhibited an increasing frequency of extreme growth reductions between 1901 and 2018, while the proportions of trees with extreme growth reductions peaked in the 1970–1980s in high‐elevation P. abies . Both for P. abies and P. sylvestris the low‐temperature‐induced extreme growth reductions declined since the 1990s, whereas events caused by drought increased in frequency. We observed higher growth volatility at the lower range of distribution compared with the upper range margin of both species. This will undoubtedly impact tree growth and vitality as the incidence of drought is expected to further increase.